Layered Oxide Cathodes for Sodium‐Ion Batteries: Phase Transition, Air Stability, and Performance - Wang, Peng‐Fei; You, Ya; Yin, Ya‐Xia; Guo, Yu‐Guo (Advanced energy materials, 2018)
The increasing demand for replacing conventional fossil fuels with clean energy or economical and sustainable energy storage drives better battery research today. Sodium‐ion batteries (SIBs) are considered as a promising alternative for grid‐scale storage applications due to their similar “rocking‐chair” sodium storage mechanism to lithium‐ion batteries, the natural abundance, and the low cost of Na resources. Searching for appropriate electrode materials with acceptable electrochemical performance is the key point for development of SIBs. Layered transition metal oxides represent one of the most fascinating electrode materials owing to their superior specific capacity, environmental benignity, and facile synthesis. However, three major challenges (irreversible phase transition, storage instability, and insufficient battery performance) are known for cathodes in SIBs. Herein, a comprehensive review on the latest advances and progresses in the exploration of layered oxides for SIBs is presented, and a detailed and deep understanding of the relationship of phase transition, air stability, and electrochemical performance in layered oxide cathodes is provided in terms of refining the structure–function–property relationship to design improved battery materials. Layered oxides will be a competitive and attractive choice as cathodes for SIBs in next‐generation energy storage devices. The recent progress in layered oxide cathodes for sodium‐ion batteries is comprehensively reviewed. Some new perspectives concentrating on phase transition, air stability, and electrochemical performance in layered cathodes are provided, in terms of refining the structure–function–property relationship to rationally design better electrode materials.